A highly sensitive glutamic acid biosensor based on the determination of NADH enzymically generated by l-glutamic dehydrogenase. Issue 51 (11th May 2016) - Lin, Xia; Wang, Qinghong; Zhu, Shu; Xu, Juanjuan; Xia, Qiao; Fu, Yingzi
Abstract : In this article, a sensitive and stereo-selective biosensor forl -glutamic acid (l -Glu) based on the electrochemiluminescence (ECL) of Ru(bpy)3 2+ has been designed by applyingl -glutamic dehydrogenase (GLDH) for enzymatic generation of NADH in situ . Abstract : In this article, a sensitive and stereo-selective biosensor forl -glutamic acid (l -Glu) based on the electrochemiluminescence (ECL) of Ru(bpy)3 2+ has been designed by applyingl -glutamic dehydrogenase (GLDH) for enzymatic generation of NADH in situ . The novel ECL Glu biosensor was prepared by immobilizing GLDH on the modified electrodes with Ru(bpy)3 2+ –platinum nanoparticles (Ru–PtNPs) and reduced graphene oxide–multiwall carbon nanotubes–Nafion (rGO–MWCNT–Nf). Fourier transform infrared spectroscopy (FT-IR), electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM) and cyclic voltammetry (CV) were employed to investigate the characteristics of different materials. In addition, the ECL technology was adopted to explore the interactions between the prepared Glu biosensor andl - ord -Glu. A remarkable difference of ECL intensity was observed when the proposed biosensor interacted withl - andd -Glu, respectively, and good responses were obtained froml -Glu in a range from 1.0 × 10 −7 M to 5.0 × 10 −3 M with a low detection limit of 3.3 × 10 −8 M (S/N = 3). The developed ECL biosensor showed satisfying sensitivity, selectivity, reproducibility and stability, therefore, it might provide a new perspective for the recognition and detection ofl -Glu.